Classroom Etiquette, Social Behavior and the Academic Performance of College of Teacher Education Students at the Laguna State Polytechnic University, Los Baños Campus, A.Y. 2015-2016 - Tamban, V E; Lazaro, M P (KnE Social Sciences, 2018)
This study aimed to determine the significant relationship between students’ classroom etiquette, students’ social behaviour and their academic performance of College of Teacher Education students at Laguna State Polytechnic University, Los Baños Campus, Academic Year 2015-2016. Descriptive correlational research design was employed in this study. The respondents of the study were the 207 Bachelor of Secondary Education (BSEd) and Bachelor of Elementary Education students (BEEd) from second year, third year and fourth year level. A valid survey questionnaire on acceptability of students’ classroom etiquette and social behavior was utilized. Mean and Chi-square were used as statistical tools. Results revealed that students’ classroom etiquette is slightly acceptable with a mean of 1.25 as well as social behavior with a mean of 2.72. Most of the respondents GWA is range form 1.75-2.00. The results determined that a significant relationship was found between the level of acceptability of students’ classroom etiquette and academic performance with the pvalue of 0.002 as well as social behavior and academic performance of the respondents with the p-value of 0.000. The researcher concluded that the students’ classroom etiquette and social behavior affect their academic performance. Those with higher level of acceptability of etiquette and social behavior performed better academically. The researchers recommended the continuous implementation of proper classroom etiquette by instructors. Seminars on values formation and social behavior may be conducted by the College to deepen the students’ values as future educators. Further study is also recommended by the researchers since it is limited only in the College of Teacher Education. Keywords: Academic Performance, Classroom Etiquette, Social Behavior